2015
DOI: 10.3109/10799893.2015.1016578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the TLR2/MyD88/NF-κB axis on corneal allograft rejection after penetrating keratoplasty

Abstract: Expression of TLR2, MyD88 and NF-κB p65 in rat corneal graft increased significantly and concurred with the allograft rejection, but were effectively inhibited by the treatment with dexamethasone and PDTC after PK. Dexamethasone could improve corneal allograft survival by the TLR2/MyD88/NF-κB axis. PDTC could suppress corneal graft rejection by inhibiting the activity of NF-κB. The TLR2/MyD88/NF-κB axis maybe a potential therapeutic target for corneal allograft rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…BM-MSCs are pluripotent stem cells with low immunogenicity, which play a role in immune regulation and stem cell homing and promote anti-inflammatory and tissue repair processes (9)(10)(11)(12)(13). It has been reported that the exosomes derived from BM-MSCs can promote the repair of corneal and conjunctival damage caused by chemical injuries and diabetic corneal epithelia; however, the underlying mechanism has not been elucidated (14)(15)(16)(17). In this study, the exosomes derived from BM-MSCs were labeled with PKH-26.…”
Section: Discussionmentioning
confidence: 99%
“…BM-MSCs are pluripotent stem cells with low immunogenicity, which play a role in immune regulation and stem cell homing and promote anti-inflammatory and tissue repair processes (9)(10)(11)(12)(13). It has been reported that the exosomes derived from BM-MSCs can promote the repair of corneal and conjunctival damage caused by chemical injuries and diabetic corneal epithelia; however, the underlying mechanism has not been elucidated (14)(15)(16)(17). In this study, the exosomes derived from BM-MSCs were labeled with PKH-26.…”
Section: Discussionmentioning
confidence: 99%